2013
DOI: 10.5812/pedinfect.9074
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Flu in Islamic Republic of Iran; A Review of Health System Response From July to November

Abstract: Background: The aspects of the epidemiology of bloodstream Candida infections including clinical features, the causal agents, underlying conditions, and risk factors have not been well-defined in Iranian pediatric patients. The aim of this observational study was to identify uncommon Candida species isolated from blood and other normally sterile specimens of the neonates and children admitted to intensive care units at Children's medical center, Tehran, Iran. Methods: The study was carried out prospectively on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Influenza causes a significant morbidity and mortality among children (1). The mortality rate of disease in Iranian infants was 7.4% in 2009 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Influenza causes a significant morbidity and mortality among children (1). The mortality rate of disease in Iranian infants was 7.4% in 2009 (2).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the Iranian health system has been moderately resilient against COVID-19, with governance being the weakest function across the country [15]. Ineffective approaches of the government and the public in managing the spread of the disease and indecisive leadership have been among the key policy challenges of the country's health system in the face of this pandemic [16].…”
mentioning
confidence: 99%